2020
DOI: 10.1016/j.foodqual.2020.103886
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable consumption among 3–5-year-old Finnish children and their parents: Is there an association?

Abstract: This study investigated the association between the home food environment and the consumption frequency of raw and cooked vegetables, berries and fruit among 3-5-year-old children and their mothers and fathers. The target group consisted of 3-5-year-old children (N=114) attending public early childhood education and care, and their parents (N=100). Cross-sectional data were collected from the parents with questionnaires assessing the home food environment, children and parents' vegetable, berry and fruit consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The FNS was also revised as the Child FNS to assess children's food neophobia as reported by parents (29) . Furthermore, some studies used the Child FNS to determine the food neophobia of children, while several studies (23,30,31) used the FNS filled in by parents instead of children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FNS was also revised as the Child FNS to assess children's food neophobia as reported by parents (29) . Furthermore, some studies used the Child FNS to determine the food neophobia of children, while several studies (23,30,31) used the FNS filled in by parents instead of children.…”
Section: Resultsmentioning
confidence: 99%
“…They also have a lower variety of FV in their diets (112) . Some studies reported this association only for vegetables (6,19,23,30,31,113,114) . Only one study conducted with Brazilian adolescents found no association between food neophobia and FV consumption (24) .…”
Section: Food Neophobia and Dietary Behavioursmentioning
confidence: 99%
“…The linear mixed-effects model analysis method allowed us to take these dependencies into account. The model consists of a fixed and random part (described in detail [ 40 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Under these temperature conditions it is possible to establish horticultural species such as; tomato, cucumber, pepper and eggplant, species for which at a commercial level there are planting materials with some characteristics that allow them to have a better adaptation to these high temperature conditions and provide acceptable final yields. This technology can also be an option to boost the consumption of F&V in children populations and thus solve the public health problem generated by nutritional deficiencies caused by diets based mainly on cereals, since F&V provide a series of vitamins, minerals and nutraceuticals properties that are essential to the healthy diet of human beings (Alzate T et al, 2017;Aune et al, 2017;Tak et al, 2019;Kähkönen et al, 2020). (Ortiz et al, 2018;Wuepper et al, 2020).…”
Section: Thermal Behaviormentioning
confidence: 99%